Efficacy and safety of first-line necitumumab plus gemcitabine and cisplatin versus gemcitabine and cisplatin in East Asian patients with stage IV squamous non-small cell lung cancer: A subgroup analysis of the phase 3, open-label, randomized SQUIRE study - Keunchil Park (2018)
© 2017 by the Korean Cancer Association. Purpose The phase 3 randomized SQUIRE study revealed significantly longer overall survival (OS) and progression-free survival (PFS) for necitumumab plus gemcitabine and cisplatin (neci+GC) than for gemcitabine and cisplatin alone (GC) in 1,093 patients with previously untreated advanced squamous non-small cell lung cancer (NSCLC). This post hoc subgroup analysis assessed the efficacy and safety of neci+GC among East Asian (EA) patients enrolled in the study. Materials and Methods All patients received up to six 3-week cycles of gemcitabine (days 1 and 8, 1,250 mg/m2) and cisplatin (day 1, 75 mg/m2). Patients in the neci+GC arm also received necitumumab (days 1 and 8, 800 mg) until disease progression or unacceptable toxicity. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated from stratified Cox proportional hazards models. Results In EA patients, there were improvements for neci+GC (n=43) versus GC (n=41) in OS (HR, 0.805; 95% CI, 0.484 to 1.341) and PFS (HR, 0.720; 95% CI, 0.439 to 1.180), consistent with the results for non-EA patients observed in the present study. The overall safety data were consistent between EA and non-EA patients. A numerically higher proportion of patients experienced serious adverse events (AEs), grade ≥ 3 AEs, and AEs with an outcome of death for neci+GC versus GC in EA patients and EA patients versus non-EA patients for neci+GC. Conclusion Although limited by the small sample size and post hoc nature of the analysis, these findings are consistent with those of the overall study and suggest that neci+GC offers a survival advantage and favorable benefit/risk for EA patients with advanced squamous NSCLC.